MiR‐20a inhibits hypoxia‐induced autophagy by targeting ATG5/FIP200 in colorectal cancer. Issue 7 (18th March 2019) - Che, Jing; Wang, Wenshan; Huang, Yu; Zhang, Lu; Zhao, Jing; Zhang, Peng; Yuan, Xianglin
Abstract: Autophagy is a highly conserved lysosome‐mediated protective cellular process in which cytosolic components, including damaged organelles and long‐lived proteins, are cleared. Many studies have shown that autophagy was upregulated in hypoxic regions. However, the precise molecular mechanism of hypoxia‐induced autophagy in colorectal cancer (CRC) is still elusive. In this study, we found that miR‐20a was significantly downregulated under hypoxia in colon cancer cells, and overexpression of miR‐20a alleviated hypoxia‐induced autophagy. Moreover, miR‐20a inhibits the hypoxia‐induced autophagic flux by targeting multiple key regulators of autophagy, including ATG5 and FIP200. Furthermore, by dual‐luciferase assay we demonstrated that miR‐20a directly targeted the 3′‐untranslated region of ATG5 and FIP200, regulating their messenger RNA and protein levels. In addition, reintroduction of exogenous ATG5 or FIP200 partially reversed miR‐20a‐mediated autophagy inhibition under hypoxia. A negative correlation between miR‐20a and its target genes is observed in the hypoxic region of colon cancer tissues. Taken together, our findings suggest that hypoxia‐mediated autophagy was regulated by miR‐20a/ATG5/FI200 signaling pathway in CRC. miR‐20a‐mediated autophagy defect that might play an important role in hypoxia‐induced autophagy during colorectal tumorigenesis.